2022
DOI: 10.3390/nu14112203
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Carica papaya and Morinda citrifolia as Perspective Food Supplements for the Treatment of Post-COVID Symptoms: Randomized Placebo-Controlled Clinical Laboratory Study

Abstract: Food supplements based on fermented Carica papaya and Morinda citrifolia, known for their immune modulating, redox balancing, and anti-inflammatory effects, were added to conventional treatment protocols prescribed to patients recovering after severe and moderate COVID-19 disease in order to alleviate long-lasting post-COVID symptoms. A randomized single-center placebo-controlled clinical laboratory study was designed and performed (total number of participants 188, with delta variant of virus 157, with omicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…Standardized fermented tropical fruits papaya ( Carica papaya L.) and mangosteen ( Garcinia mangostana Linn.) syrups of food grade [ 50 , 51 , 52 , 53 , 54 ] were used as active ingredients for hair care cosmetic products (they are classified as raw materials for cosmetics by the International Cosmetic Ingredient Index (INCI)). Their concentrations in the experimental lotion were equal to 2.0% w / w for each fermented fruit, and caffeine concentration was 0.5% w / w (lotion’s internal code, MEDENA-1324-HL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized fermented tropical fruits papaya ( Carica papaya L.) and mangosteen ( Garcinia mangostana Linn.) syrups of food grade [ 50 , 51 , 52 , 53 , 54 ] were used as active ingredients for hair care cosmetic products (they are classified as raw materials for cosmetics by the International Cosmetic Ingredient Index (INCI)). Their concentrations in the experimental lotion were equal to 2.0% w / w for each fermented fruit, and caffeine concentration was 0.5% w / w (lotion’s internal code, MEDENA-1324-HL).…”
Section: Methodsmentioning
confidence: 99%
“…Fermented tropical fruits, such as papaya, noni, mangosteen, pineapple, berries, etc., seem to be a unique source of both plant-derived low molecular weight biomolecules (secondary metabolites) and fermenting microbe-associated actives with pro- and prebiotic properties [ 47 , 48 , 49 ]. Plant-derived secondary metabolites (polyphenols/terpenes/alkaloids) and microbial exometabolites/membrane components of fermented tropical fruits are known as highly bioavailable biomolecules causing skin and hair improving effects—antioxidant, wound healing, anti-inflammatory antidiabetic, antiacne, skin/hair microbiota balancing, hair growth-promoting, and hair loss-inhibiting [ 50 , 51 , 52 , 53 , 54 ]. The molecular/cellular mechanisms of these health effects have been intensely studied in in vitro and in vivo preclinical experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In an RCT that enrolled 188 patients and 25 controls, Kharaeva et al showed that the use of Carica papaya and Morinda citrifolia supplements reduced post-COVID symptoms, with increased leukocyte phagocytic capacity, antioxidant activity, and ATP content [ 153 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…There are abundant noni germplasm resources in south China. In recent decades, noni fruit has attracted much research attention because of its extensive biological and pharmacological properties including anticancer ( Ma et al, 2020 ), anti-inflammatory ( Kharaeva et al, 2022 ), anti-oxidant ( Wang et al, 2022 ), and immune modulatory effects ( Ezzat et al, 2021 ). Dietary supplementation of noni fruit has been found to strengthen humonal immune response in broiler chickens ( Sunder et al, 2015 ), to enhance the anti-oxidant enzyme activities in serum of calves ( Anantharaj et al, 2017 ), and to counteract the adverse effect of high-fat intake on yellow catfish growth ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%